Diversity of land use restrictions impact on social life - Petrakovska, Olga; Mykhalova, Mariia (International Conference “Environmental Engineering”, 2023)
The purpose of the study is to investigate of diversity of land use restrictions and their impact on social life. The analysis and synthesis, comparison and system methods were used during this study. The following tasks are aimed to achieve the goal: to perform the analysis of land use restrictions diversity; to aggregate and structure the land use restrictions; categorize the land use restrictions; to research the impact of land use restrictions on social life. The classification of land use restrictions is proposed de-pends on different classification features. The results of the study illustrate the need for further determination of the assessment of the impact of restrictions on social life.